PEMERIKSAAN TEKANAN DARAH DAN TES BUTA WARNA PADA MAHASISWA BARU DI SALAH SATU PTS KOTA PALEMBANG TAHUN 2023 - Sulastina, Nur Afni; Oktaviana Hasibuan, Tri; Fitri, Melly; Septiani , Rima; Eliyani , Yunita (Avicenna: Jurnal Ilmiah, 2023)
Background: Health examinations can be carried out at government or private laboratories or free health education institutions. A person's blood pressure is influenced by several factors, such as changes in body position and physical activity. However, color often causes problems for sufferers both in daily activities and when sufferers want to pursue higher education or apply for certain types of work. The aim is to provide blood pressure checks and color blindness tests for new students at PTS X Palembang City in 2023. Method: research using quantitative methods with a Cross Sectional research design, carried out at the PTS X Laboratory, Palembang City on September 7 2023. The research population was 96 students and the research sample was 96 students using total sampling technique, data collection using checklist sheets and data analysis using univariate and bivariate analysis. Results: Based on the results obtained from 96 students at PTS Blood pressure examination results were abnormal 51.0%, normal 49.0%. The color blindness test results, which were 1.0% color blind, were 99.0% normal. From the majors, the Public Health major got 57.3%, ATLM 42.7%. There is a significant relationship between the color blindness test and gender (p value 0.003 and OR 0.900). There was no relationship between gender, PTS major and blood pressure. There is no relationship between major and color blindness test. Conclusion: Blood pressure checks and especially color blindness should be given early so as not to affect learning achievement, educational paths and future career development.   Keywords : Health Checkup, Blood pressure, Color blindness